Lifelong Bilingualism Functions as an Alternative Intervention for Cognitive Reserve Against Alzheimer's Disease - Liu, Haiqing; Wu, Longhuo (Frontiers in Psychiatry, 2021)
Bilingualism has been reported to significantly delay the onset of dementia and plays an important role in the management of Alzheimer’s disease (AD), which induces impairment in the brain network and cognitive decline. Cognitive reserve is associated with the adaptive maintenance of neural functions by protecting against neuropathology. Bilingualism acts as a beneficial environmental factor contributing to cognitive reserve, although some potential confounding variables are still needed to be further elucidated. In this article, the relationships between bilingualism and cognitive reserve are discussed, interpreting the advantage of bilingualism in protecting against cognitive decline. In addition, the review on the possible brain and biochemical mechanisms of bilingualism for supporting the advantageous effects of bilingualism on delaying the onset of dementia is involved. Effectively, bilingualism can be considered as a pharmacological intervention without any side effects. However, the investigation on the pharmacological parameters of bilingualism is still at the beginning stage.